INTEGRATING LOCAL WISDOM INTO INTERCULTURAL EFL PEDAGOGY: BRIDGING GLOBAL ENGLISH AND INDONESIAN CULTURAL VALUES - Anugerah Febrian Syam (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study aims to examine how Indonesian local wisdom can be reconceptualized as an epistemic framework in intercultural EFL pedagogy to bridge Global English and Indonesian cultural values. The research employed a qualitative approach using Critical Ethnography conducted over one academic semester. Data were collected through classroom observations, in-depth interviews, focus group discussions, and document analysis involving third-year EFL students at a private university in Indonesia. The data were analyzed using Reflexive Thematic Analysis combined with Critical Discourse Analysis to identify patterns of meaning, power relations, and identity negotiation in classroom interactions. The results show that the integration of local wisdom in intercultural EFL pedagogy functions as an epistemic anchor that shapes students’ intercultural understanding through collective values such as cooperation and social harmony. Students actively negotiate the normativity of Global English rather than accepting it as an absolute standard, resulting in the emergence of dialogic intercultural classroom spaces and the formation of hybrid intercultural identities. These findings indicate a shift from adaptive pedagogy toward reflective and critical intercultural pedagogy that recognizes the legitimacy of local knowledge in global English learning practices. In conclusion, integrating local wisdom into intercultural EFL pedagogy not only contextualizes language learning but also promotes epistemic justice by enabling students to mediate between global linguistic demands and local cultural identities.